An assessment of carbon footprint at Universiti Teknologi MARA Seri Iskandar Perak, Malaysia / Nor IzanaMohd Shobri ... [et al.] - Nor Izana, Mohd Shobri; Wan Noor Anira, Wan Ali @ Yaacob; Norizan, Mt Akhir; Siti Rasidah, Md Sakip (2015)
Climate change and global warming have worsenedsince over the past year due to the greenhouse gas emission. Evidences show one of the main factors that contributes to global warmingis the impact of carbon footprint. Human activities are the causes of a great deal of carbon footprint. Therefore, the purpose of this study is to assess the carbon footprint emission at UniversitiTeknologi MARA (UiTM) Seri Iskandar, Perak. The study focuses on two categories specifically on electrical power and transportation usage that contribute to carbon footprint emission. A survey on transportation was conducted by distributing questionnaire to the staffand students within the university. Meanwhile for electrical power consumption, the study used monthly electricity bills to measure the amount of energy consumed.Data was collected and calculated with the formula developed by Green House Gas protocol, resulted in the total carbon footprint produced by UiTM Seri Iskandar Perak for the year 2014. The result of the study is hoped to provide guidelines and strategies for the university to reduce the carbon footprint emission at UiTM Seri Iskandar, Perak.